Relation between acquisition of lexical concept and joint attention in children with autism spectrum disorder without severe intellectual disability. - Masuhiko Sano; Tetsu Hirosawa; Mitsuru Kikuchi; Chiaki Hasegawa; Sanae Tanaka; Yuko Yoshimura (PLoS ONE, 2022)
In children with autism spectrum disorder (ASD), impairment of joint attention and language function are observed frequently from early childhood. Earlier reports have described these two phenomena as mutually related. For this study, developing past research, the relation between joint attention and the ability of conceptual inference is examined in 113 Japanese children (67.9 months mean age, 75% male) with ASD. We calculated Pearson's correlation coefficients between their Joint attention abnormality evaluated by ADOS-2 and "Riddle" subscale in K-ABC, then they are negatively correlated: r (104) = -.285. A larger abnormality of joint attention is associated with a lower ability of conceptual inference. New findings were obtained indicating that, in children of this age group with ASD, the degree of joint attention impairment is correlated negatively with conceptual inference ability, but not with expressive and receptive language abilities. Consideration of the mechanism of this relation is presented in this report.